Analysis of Students' Metacognition in Solving Open Ended SPLDV Problems Based on Sensing-Intuition Personality - Anjani, Diva Setyo; Trapsilasiwi, Dinawati; Murtikusuma, Randi Pratama; Oktavianingtyas, Ervin; Putri, inge Wiliandani Setya (Department of Mathematics Education , University of Jember, 2021)
This research purpose to describe metacognition in solving Open Ended SPLDV Problems Based on Sensing Intuition personality. This research type is qualitatif descriptive conducted in class VIII I SMP Negeri 1 Purwosari. Subjects of this research consist of 3 students with Sensing personality and 3 students with Intuition personality selected based on the highest score on personality type. Six students will solve Open Ended problem and inteview. The results showed that students sensing type receive information based on the facts, while students Intuition type personality found a correlation based on information. Students Sensing type only solve Open Ended problems using two different methods the teacher had been taught, while students Intuition type able to solve Open Ended problems using new methods and able to explain solution more than two correctly answers. On the worksheet students Sensing type tend to be systematic, while students Intuition type tend to be not systematis. Although there is a difference metacognition activities in solving Open Ended SPLDV problems, students with Sensing and Intuition personality able to meet all indicator metacognition planning, monitoring, and evaluating.